2019
DOI: 10.1590/s1519-9940200182019
|View full text |Cite
|
Sign up to set email alerts
|

Performance and feed efficiency of beef cattle fed high energy diet with probiotic consortium technology

Abstract: SUMMARY The objective of this study was to evaluate the effect of probiotic consortium on feed intake, feeding behavior, feed efficiency, fecal score, weight gain and carcass traits in finishing Nellore heifers fed high energy diets in feedlot. Twenty-four Nellore heifers were distributed in 12 pens with two animals each, being six pens per treatment. In the control treatment (CON) the animals were fed exclusively with the base diet, which contained 35% corn silage and 65% concentrate. In the treatment with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Similarly, steers fed a forage-based diet separately supplemented with L. acidophilus (RumaCell®, Pacer Technologies INC., Murtaugh, ID) and monensin during 42 days, showed greater BW and ADG values in the presence of probiotic alone [22]. In other study, in the absence of growth promoter, BW and ADG increases by 33.8 and 12.5%, respectively, were described as greater than that of the control when a probiotic consortium (LAB 3 × 10 5 + yeasts 1 × 10 6 CFU/mL) was supplemented during 93 days to finishing Nellore heifers [16]. In addition, calves' diet supplemented by a multi-strain probiotic (seven bacterial strains + two yeasts; 2 × 10 9 CFU/g) during eight weeks, and ewes administered with S. cerevisiae and Bacillus subtilis + Lactobacillus casei (10 10 -10 11 CFU/day) during three months after parturition, showed greater ADG values compared to the control [23,24].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Similarly, steers fed a forage-based diet separately supplemented with L. acidophilus (RumaCell®, Pacer Technologies INC., Murtaugh, ID) and monensin during 42 days, showed greater BW and ADG values in the presence of probiotic alone [22]. In other study, in the absence of growth promoter, BW and ADG increases by 33.8 and 12.5%, respectively, were described as greater than that of the control when a probiotic consortium (LAB 3 × 10 5 + yeasts 1 × 10 6 CFU/mL) was supplemented during 93 days to finishing Nellore heifers [16]. In addition, calves' diet supplemented by a multi-strain probiotic (seven bacterial strains + two yeasts; 2 × 10 9 CFU/g) during eight weeks, and ewes administered with S. cerevisiae and Bacillus subtilis + Lactobacillus casei (10 10 -10 11 CFU/day) during three months after parturition, showed greater ADG values compared to the control [23,24].…”
Section: Discussionmentioning
confidence: 76%
“…have been reported as a desirable alternative to antibiotic growth promoters, supporting cattle health and growth promotion [14,15]. Specifically, a number of studies have reported the use of probiotic lactic acid bacteria (LAB) to improve meat cattle production performance [16,17]. Therefore, the present study aimed to investigate the effect of probiotic lactobacilli previously identified and characterized from a feedlot environment [4,18] in the presence or absence of monensin by using body weight (BW) and average daily gain (ADG) changes as indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Given the close relationship between the diversity of the rumen microbiome and an animal's ability to obtain and use nutrients, ideal growth promoters should minimally affect the animal's natural microbiome while enhancing growth, health, and reproduction (Breves et al, 2000;Mostafa et al, 2014) [30,94] . Numerous animal probiotics have demonstrated the ability to enhance feed efficiency (Moreira et al, 2019) [93] , improve growth performance (Tripathi and Karim, 2010; Didarkhah and Bashtani, 2018) [144,49] , enhance nitrogen retention (Schofield et al, 2018) [125] , and lower the likelihood of intestinal infections [10,144,132,49] . Probiotics play a crucial role in enhancing the growth of both rumen and intestinal epithelial cells, thus improving the capacity for nutrient uptake.…”
Section: Probiotics Strategies For Stimulating Dairy Animal Growthmentioning
confidence: 99%
“…Since the diversity of the rumen microbiome is closely related to the animal’s ability to acquire and assimilate nutrients, ideal growth promoters would have only a negligible impact on the animal’s natural microbiome, while enhancing the animal’s growth, well-being and reproduction ( Breves et al, 2000 ; Mostafa et al, 2014 ). Many animal probiotics have been shown to improve feed efficiency ( Moreira et al, 2019 ), growth performance ( Tripathi and Karim, 2010 ; Didarkhah and Bashtani, 2018 ), nitrogen retention ( Schofield et al, 2018 ) and also reduced the risk of intestinal infections ( Aldana et al, 2009 ; Tripathi and Karim, 2010 ; Signorini et al, 2012 ; Didarkhah and Bashtani, 2018 ).…”
Section: Probiotics To Promote the Growth Of Dairy Animalsmentioning
confidence: 99%